Role of GPR55 receptor in bovine sperm capacitation - Lottero-Leconte, Raquel; Lara, Angela; Plaza, Jessica; Arroyo-Salvo, Camila; Bogetti, María Eugenia; Ynsaurralde Rivolta, Amanda Eugenia; Dellavalle, Franco Alejandro; Sengiali, Fiamma; Cetica, Pablo; Rio, Sofía; Zalazar, Lucia; Cesari, Andreína; et al. (Wiley, 2025)
Background: Endocannabinoids like anandamide (AEA), among other lipids, are recognized signaling molecules that participate in reproductive events. Objectives: Our aims were to characterize orphan G protein-coupled receptor (GPR55) presence; investigate GPR55 activation by AEA and determine GPR55 role in the bovine sperm function. Materials and methods: GPR55 presence was assessed by immunocytochemistry. Protein kinase A (pPKA) and PKC (pPKC) substrates, pERK1/2, G/F-actin were determined by Western blotting, activation of RAC-1 by pull-down assay, F-actin and acrosomal exocytosis by fluorescence microscopy, sperm motility by optic microscopy and computer-aided sperm analysis and fertilizing ability by in vitro fertilization (IVF). Results: We detected GPR55 in spermatozoa at T0, after incubation in non-capacitating and capacitating (presence of AEA) conditions and upon release from oviductal epithelia. AEA induced an increase in pPKA and pPKC, while CID16020046 (CID), selective GPR55 antagonist, prevented this effect. Incubation with H89, PKA inhibitor, significantly decreased pPKC, while Gö6983, a PKC inhibitor, partially reduced pPKA. pPKA remained elevated at 15- and 45-min incubation, while pPKC decreased at 15 and increased at 45 min. CID prevented pPKC increase at 5 and 45 min and decreased pPKA at 45 min. RAC-1 and F-actin increase induced by AEA was prevented by CID. Variations in two progressive motility kinematic parameters were observed with AEA and/or CID. Sperm pretreatment with AEA increased the rate of cleaved embryos and CID prevented this effect. Discussion: We demonstrated that GPR55 activation by AEA induces time-dependent signaling pathways involving pPKA and pPKC during bovine sperm capacitation. AEA regulates actin polymerization through GPR55 activation, suggesting the receptor participates in cytoskeleton remodeling, and yielded higher IVF rates. Also, sperm pre-incubation with molecules like AEA involved in capacitation could improve the embryo development. Conclusion: We have demonstrated GPR55 presence in bovine spermatozoa. The regulation of PKA and PKC and of molecules associated with cytoskeletal dynamics, such as RAC-1 and actin, by GPR55 is closely related to sperm motility and acrosomal exocytosis.